Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Dengan Usia Sebagai Moderator - Arry Widodo; Rennyta Yusiana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The basis of a company's marketing strategy is to study consumer behavior, including the consumer decision-making process. Before the emergence of consumer purchasing decisions have an interest first. The purpose of this study is to determine the relationship between product knowledge and product involvement with purchasing decision making. In addition, this study also determines the role of halal brand awareness as a moderating variable in influencing the relationship between product knowledge and product involvement with purchasing decision making. This study aims to determine the relationship between the influence of ice cream product quality on purchasing decisions. In addition, this study also determines the role of age as a moderating variable in influencing the relationship between product quality and purchasing decision making. The number of samples is 400 respondents with a purposive sampling technique through a Likert scale questionnaire. Data analysis used descriptive and smart-PLS. The results showed that product quality had a significant positive effect on purchasing decisions. When consumers are faced with reviews related to trust and emotional purchase decisions on an ice cream product. Additionally, the moderating effect of consistent reviews was stronger for female consumers than for male consumers. Researchers hope that this research can enrich the understanding of how consistent reviews play a role in consumer purchasing decisions. Furthermore, in the behavior of consumers who make purchasing decisions on a product, look at the benefits and the resulting impact in determining purchase attitudes on an ice cream product.